PENGARUH PELATIHAN KERJA, MOTIVASI KERJA DAN PENGAWASAN TERHADAP KINERJA KARYAWAN: Studi Kasus di Dinas Kebakaran dan Penyelamatan Kabupaten Badung - I G Ag, Sasih Gayatri; Ni Luh Sili Antari; Ni Luh Yuni Astuti (Journal Research of Management, 2021)
This study aims to analyze the effect of job training, work motivation and supervision on employee performance in the Fire and Rescue Agency of Badung Regency. Data collection techniques in this study used a questionnaire distributed to respondents using a Likert scale. Types and sources of data used in this study are types of quantitative data and primary data sources. The sampling technique in this study uses random sampling techniques and data analysis techniques in this study using the validity and reliability test, the classic assumption test and the multiple linear regression test. Based on the results of the study show that 1) Job training has a positive and significant effect on employee performance in the Badung Fire Department, 2) Work motivation has a positive and significant effect on employee performance in the Badung Fire Department and 3) Supervision has a positive and significant effect on performance employee at the Badung District Fire Department. The implication of the research in this study is that every decision and policy adopted by the agency will always have an impact on employee performance, so the right policies are needed to reduce the existence of fraud in the implementation of the duties and obligations of each division of employees.